The Impact of BPJS Contribution Increases on Health Services - Kowel Gonjales Sinaga; Husnil Hidayat (Journal of Health Management, Administration and Public Health Policies, 2024)
Presidential Regulation Number 19 of 2016 concerning Health Insurance stated on April 1, 2016, that BPJS contributions will increase. This increase in BPJS contributions has caused many people to complain, especially independent BPJS patients, and this can affect the satisfaction of BPJS participants. This research is qualitative, using a systematic review approach technique. The articles used in this study are full-text articles with an observational study design (cross-sectional, cohort, and case control) published from 2014 to 2024. The independent variables include the level of BPJS contribution increase status, and the dependent variable is the quality of health services. Article data collection was carried out by searching for articles in the Google Scholar, PubMed, and Science Direct database search databases. This study shows that the increase in BPJS Health contributions has an important role in determining the behaviour of using health services and has implications for economic and social aspects. The contributions paid by participants affect their decision to use health services, as well as affect the class of contributions chosen. Thus, it can be concluded that the increase in BPJS contributions affects BPJS participant patient satisfaction. Keywords: Contributions, BPJS, Health Services